DYNAMICS OF GRAPHITE EXTRACTION AND REALIZATION IN UKRAINE AND WORLDWIDE - Zagnitko, V.; Lyzhachenko, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Graphite, as one of the most important components of modern technology and production, played for any country an important role. The properties of this mineral allow you to use it as and carbon in General, in all sectors of the national economy, science and technology. The work covers the main changes in the industrial sectors of consumption and production of graphite in Ukraine and in the world.